Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Zhang, Min; Liu, Chong; Yuan, Xiao-Qiong; Yao, Wen; Yao, Qing-Yun; Huang, Yong; Li, Ni-Jie; Deng, Yan-Ling; Chen, Pan-Pan; Miao, Yu; Cui, Fei-Peng; Li, Yu-Feng; et al. (Environmental pollution (1987), 2023)
Phthalates, as endocrine disrupting chemicals that can alter the endogenous hormones, may be involved in the incidence of endometrial polyp, a benign hormone-dependent condition. We conducted a pilot case-control study from the Tongji Reproductive and Environmental (TREE) cohort to investigate the associations between phthalate exposures and the risk of endometrial polyp. A total of 40 endometrial polyp patients were matched to 80 controls by age and body mass index in the ratio of 1:2. Two spot urine samples from each subject were quantified for eight phthalate metabolites to enhance exposure assessment. The conditional logistic regression and quantile-based g-computation models were separately used to explore the associations between individual and mixture of urinary phthalate metabolites and the risk of endometrial polyp. After adjusting for covariates, individual chemical analyses showed that urinary monobenzyl phthalate (MBzP), mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), mono(2-ethyl-5-carboxypentyl) phthalate (MECPP), mono(2-ethyl-5-oxohexyl) phthalate (MEOHP), mono(2-ethylhexyl) phthalate (MEHHP) and the sum of di(2-ethylhexyl) phthalate (ΣDEHP) were associated with increased risks of endometrial polyp, with adjusted odds ratios ranging from 2.62 (95% CI: 0.88, 7.84) for MECPP to 6.96 (95% CI: 1.87, 25.87) for ΣDEHP comparing the extreme exposure categories (all P for trends <0.05 or = 0.057). These associations still persisted when these exposures were modeled as continuous variables. Chemical mixture analyses showed that a simultaneous one-quartile increase in concentrations of eight phthalate metabolites was associated with an elevated odds ratio of 3.14 (95% CI: 1.49, 6.60) in endometrial polyp. Our data suggests that exposure to individual benzylbutyl phthalate (BBzP) and DEHP, as well as mixture of phthalates is associated with increased risk of endometrial polyp. This may inform public health recommendations and policies to avoid phthalate exposures for improving female reproductive health. [Display omitted] •Benzylbutyl phthalate and di(2-ethylhexyl) phthalate exposures were associated with increased risk of endometrial polyp.•Exposure to phthalate mixtures was associated with increased risk of endometrial polyp.•Mono(2-ethyl-5-hydroxyhexyl) phthalate was the largest positive contributor to the risk of endometrial polyp.